Utilization of Canva as a Learning Aid in Informatics for Middle School Students - Agustini, Sherly (Engineering and Technology International Journal, 2023)
This research explores the utilization of the Canva application as an instructional aid in computer science education at the junior high school level with the aim of identifying how Canva can be effectively used in the learning process and its impact on students' understanding and engagement in computer science subjects. The research method employed is descriptive qualitative with data collected through observation and questionnaires. The findings indicate that the use of Canva enhances student engagement and understanding of computer science concepts. Students responded positively to Canva, feeling comfortable and enthusiastic about using the application as a learning tool. Challenges in Canva implementation include the availability of technological devices and teacher training. This study recommends providing adequate training for teachers, integrating Canva into the curriculum, and improving technology infrastructure in schools.